IMPLEMENTATION OF PROBLEM-BASED INSTRUCTION LEARNING MODEL USING MEDIA KOTAK DAN KARTU MISTERI TO IMPROVE STUDENT LEARNING OUTCOMES - Pujianto .; Janelle L. Juneau (JURNAL HANDAYANI PGSD FIP UNIMED, 2017)
Abstract : Implementation Of Problem-Based Instruction Learning Model Using Media Kotak Dan Kartu Misteri To Improve Student Learning Outcomes. The purpose of this research is to improve the quality of natural science learning through Problem-Based Instruction learning model using Kotak dan Kartu Misteri (KOKAMI) media in fourth students of SD Negeri Dukuh 01 Salatiga. The subjects of this research are 37 fourth grade students of SD Negeri Dukuh 01 Salatiga. The collecting data techniques used were test and non-test. Data analysis techniques used were quantitative and qualitative analysis. The result of the research in the first cycle was the natural science learning outcomes of 27 students or 73% have reached the score limit and the natural science learning outcomes of 10 students or 27% have not reached the score limit yet. In the second cyle, the learning outcomes of 37 students or 100% have reached the score limit and none of the student got score below the limit. Keywords : Problem-Based Instruction, Kotak dan Kartu Misteri,                    Learning Outcomes and Natural Science